Multiculturalism in Samuel Shimon An Iraqi in Paris novel - طهماسبي, عدنان; اعرجي, فاطمة (Al-Adab Journal, 2018)
Concerning of the importance of the study of multiculturalism and dynamic identities that arise for groups, ethnic minorities and immigrants may find difficulty and trouble in agreement with the host culture and society in which they found themselves. At the level of cultural identity, those minorities established a distinctive special culture which can be described as an unfinished project and a constant growing process. Therefore, Samuel Shimon’s An Iraqi in Paris novel has slowed down on this hybridity and on the spirit of the age, rejecting the monotheism. In its narrative level, it produced a hostile text to the cultural tyranny that orders the one voice and rejecting the multitudes, focusing instead on the idea of knowing others leads for knowing ourselves and the assimilation of others is a successful pursuit of identity through distinctions. Thus, we may find different patterns of identity in the central character of this novel, patterns that may be quite different but contradictory, offering a diverse cultural opportunities and possibilities. These possibilities are echoed by the postcolonial critics who have dealt with ethnographic literature as a result of diversity and multiple cultures.